2013
DOI: 10.5194/hess-17-2069-2013
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoclimatological perspective on river basin hydrometeorology: case of the Mekong Basin

Abstract: Abstract. Globally, there have been many extreme weather events in recent decades. A challenge has been to determine whether these extreme weather events have increased in number and intensity compared to the past. This challenge is made more difficult due to the lack of long-term instrumental data, particularly in terms of river discharge, in many regions including Southeast Asia. Thus our main aim in this paper is to develop a river basin scale approach for assessing interannual hydrometeorological and disch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…TC can induce a large amount of instantaneous precipitation in the MB by extreme rainfall events that may cause flooding. Meanwhile, the ENSO is associated with the interannual hydrometeorology and discharge variability (Räsänen and Kummu, ; Räsänen et al, ), which could also lead to extreme water‐related events. Due to the climate change, the non‐stationary atmospheric circulations could be a reason for increasing hydroclimate change in the MB (Delgado et al, ).…”
Section: Study Area and Datamentioning
confidence: 99%
“…TC can induce a large amount of instantaneous precipitation in the MB by extreme rainfall events that may cause flooding. Meanwhile, the ENSO is associated with the interannual hydrometeorology and discharge variability (Räsänen and Kummu, ; Räsänen et al, ), which could also lead to extreme water‐related events. Due to the climate change, the non‐stationary atmospheric circulations could be a reason for increasing hydroclimate change in the MB (Delgado et al, ).…”
Section: Study Area and Datamentioning
confidence: 99%
“…Huang et al, 2004). Thus, a hydrometeorological study linking with the ENSO cycle will help to better model the local flow regime from a large-scale perspective Räsänen et al, 2013).…”
Section: Inflows To the Mlyrmentioning
confidence: 99%
“…Räsänen et al . () also concluded that the Mekong has experienced exceptional levels of interannual variability during the post‐1950 period. Hanh and Furukawa () investigated data from seven tide gauges recording sea‐level changes across the coasts of Vietnam.…”
Section: Introductionmentioning
confidence: 96%